Context and the VSL: evidence from a stated preference study in Italy and the Czech Republic - Anna Alberini; Milan Ščasný (Fondazione Eni Enrico Mattei (FEEM), 2010)
We report on the results of a survey based on conjoint choice experiments that was specifically designed to investigate the effect of context on the Value of a Statistical Life (VSL), an important input into the calculation of the mortality benefits of environmental policies that reduce premature mortality. We define 'context' broadly to include i) the cause of death (respiratory illness, cancer, road traffic accident), ii) the beneficiary of the risk reduction (adult v. child), and iii) the mode of provision of the risk reduction (public program v. private good). The survey was conducted following similar protocols in Italy and the Czech Republic. When do not distinguish for the cause of death, child and adult VSL are not significantly different from one another in Italy, and the difference is weak in the Czech sample. When we distinguish for the cause of death, we find that child and adult VSLs are different at the 1% level for respiratory illnesses and road-traffic accidents, but do not differ for cancer risks. We find evidence of a 'cancer premium' and a 'public program premium.' In both countries, the marginal utility of income is about 20% lower among wealthier people, which makes the VSL about 20% higher among respondents with incomes above the sample average. The discount rate implicit in people's choices is effectively zero. We conclude that there is heterogeneity in the VSL, and that such heterogeneity is primarily driven by risk characteristics and mode of delivery of the risk reduction, rather than by individual characteristics of the respondent (e.g., income and education). For the most part, our results do not disagree with environmental policy analyses that use the same VSL for children and adults, and that apply a cancer premium.
Keywords: I18; J17; K32; Q51; 330; VSL; Conjoint Choice Experiments; Mortality Risk Reductions; Cost-benefit Analysis; Forced Choice Questions